1994
DOI: 10.1136/gut.35.11.1659
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction of pancreatic elastase and leucocytes to produce oxygen radicals and its implication in pancreatitis.

Abstract: Many previous reports using experimental animal models of pancreatitis have suggested that oxygen free radicals play an important part in initiation and development of pancreatitis. Infiltration of inflammatory cells -that is, neutrophils, lymphocytes, and monocytes -has been seen in damaged pancreatic glands of animal models and patients with pancreatitis. As neutrophils are known to be the highest producer of oxygen free radicals among these inflammatory cells, it seems plausible that oxygen free radicals pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Recent studies have demonstrated NAD(P)H oxidase activity (34) and inhibition of superoxide production by DPI in a pancreatic cancer cell line (35). Current evidence suggests that ROS production is enhanced in neutrophils obtained from patients with acute pancreatitis (36), and ROS derived from neutrophil NADPH oxidase may play an important role in implementing damage in experimental acute pancreatitis (37). The lack of effect of DPI observed in the present study would strongly suggest that acinar cell NAD(P)H oxidase is not responsible for the generation of ROS by menadione.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated NAD(P)H oxidase activity (34) and inhibition of superoxide production by DPI in a pancreatic cancer cell line (35). Current evidence suggests that ROS production is enhanced in neutrophils obtained from patients with acute pancreatitis (36), and ROS derived from neutrophil NADPH oxidase may play an important role in implementing damage in experimental acute pancreatitis (37). The lack of effect of DPI observed in the present study would strongly suggest that acinar cell NAD(P)H oxidase is not responsible for the generation of ROS by menadione.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the superoxide production by neutrophils treated with PMA in pancreatitis patients was significantly higher than in healthy controls [5]. Among ROS, superoxide is the first reduction product of molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are known to be the most intense producers of reactive oxygen species (ROS) among inflammatory cells. Actually, the ROS production of neutrophils obtained from patients with acute pancreatitis was enhanced [5]. The antioxidant status (plasma levels of glutathione and ascorbic acid) was decreased in patients with chronic pancreatitis [6].…”
Section: Introductionmentioning
confidence: 95%
“…In a limited number of previous studies, long-term oral administration of TQ may be effective in diseases where infl ammation and reactive oxygen species (ROS) are a prominent factor, but the pathophysiology of this effect is unclear (17,18). Although several studies show that it is not clearly elucidated in the pathogenesis of acute pancreatitis, infl ammation and ROS have an important role in the pathogenesis (19,20). The literature search shows that there is no study related to TQ effect on infl ammation, oxidative status and cytoprotective effect in acute pancreatitis model.…”
Section: Tab 1 Dna Damage Values Oxidative Stress Parameters and Bmentioning
confidence: 99%